Ventilation and cave air pCO2 in the Bunker-Emst cave system (nw Germany): implications for speleothem proxy data - Riechelmann, Sylvia; Breitenbach, Sebastian F. M.; Schröder-Ritzrau, Andrea; Mangini, Augusto; Immenhauser, Adrian (Journal of cave and karst studies, 2019)
Cave air pCO(2) (carbon dioxide partial pressure) is, along with drip rate, one of the most important factors controlling speleothem carbonate precipitation. As a consequence, pCO(2) has an indirect but important control on speleothem proxy data (e.g., elemental concentrations, isotopic values). The CO2 concentration of cave air depends on CO2 source(s) and productivity, CO2 transport through the epikarst and karst zone, and cave air ventilation. To assess ventilation patterns in the Bunker-Emst Cave (BEC) System, we monitored the pCO(2) value approximately 100 m from the lower entrance (Bunker Cave) at bi-hourly resolution between April 2012 and February 2014. The two entrances of the BEC system were artificially opened between 1860-1863 (Emst Cave) and 1926 (Bunker Cave). Near-atmospheric minimum pCO(2) dynamics of 408 ppmv are measured in winter, and up to 811 ppmv are recorded in summer. Outside air contributes the highest proportion to cave air CO2, while soil, and possibly also ground air, provide a far smaller proportion throughout the whole year. Cave air pCO(2) correlates positively with the temperature difference between surface and cave air during summer and negatively in winter, with no clear pattern for spring and autumn. Dynamic ventilation is driven by temperature and resulting density differences between cave and surface air. In summer, warm atmospheric air is entrained through the upper cave entrance where it cools. With increasing density, the cooled air flows toward the lower entrance. In winter, this pattern is reversed, due to cold, atmospheric air entering the cave via the lower entrance, while relatively warm cave air rises and exits the cave via the upper entrance. The situation is further modulated by preferential south-southwestern winds that point directly on both cave entrances. Thus, cave ventilation is frequently disturbed, especially during periods with higher wind speed. Modern ventilation of the BEC system-induced by artificially openings-is not a direct analogue for pre-1860 ventilation conditions. The artificial change of ventilation resulted in a strong increase of delta C-13(speleothem) values. Prior to the cave opening in 1860, Holocene delta C-13(speleothem) values were significantly lower, probably related to limited ventilation due to the lack of significant connections between the surface and cave. Reduced ventilation led to significantly higher pCO(2) values, minimal CO2 degassing from drip water and low kinetic isotope fractionation. Both modern and fossil speleothem precipitation rates are driven by water supply and carbonate saturation, and not by cave air pCO(2). Today, pCO(2) variability is too small to affect carbonate precipitation rates and the same is likely true for pCO(2) variability prior to artificial opening of the cave. Thus, fossil speleothems from BEC System are likely more sensitive to temperature and infiltration dynamics. The Bunker-Emst Cave System, therefore, represents different ventilation patterns and their influence on speleothem proxy data in an exemplary manner, and it may serve as a template for other cave systems.
Das p in pCO2 ist kursiv geschrieben, die 2 ist tiefgestellt
Gesehen am 03.01.2019